Determining Digital Maturity Among Ict Users In Malaysia - Azman, H; Salman, A; Razak, NA; Hussin, S; Hasim, MS; Abu Hassan, U (Natl Univ Malaysia, Fac Social Sciences & Humanities, 2024)
With the fast development in ICT, the need for digital maturity becomes increasingly important. Measuring ICT maturity has always been on the infrastructural, applications, and ICT Policy. Taking a different orientation, the present study views ICT maturity of the individual users vis a vis the ICT tools as a solid foundation for successful digital maturity in a digital economy. This paper aims at determining the level of digital maturity among ICT-Mobile Phone (smart phone and internet) users by looking at the intensity of usage of smart phone applications (apps) and functions and the level of indispensability of internet and its related characteristics and functions. A nationwide survey was conducted among 2124 respondents based on the population ratio of the main ethnic groups in Malaysia. Data were analysed using SPPS 20.0 and both descriptive and inferential analysis are applied to analyse the data. The results revealed that the smart phone functions, facilities, and apps which are mostly used include social media (Facebook/Twitter), instant messaging (WhatsApp/Viber/Skype), Wi-Fi, downloading apps from 'Play Store' or 'App Store' and camera. The findings also indicated that a fast internet service, availability of internet at anytime and anywhere and the access to internet content without limit are the most indispensable characteristics and functions of internet for the users. The results implied that the respondents are above average in digital maturity in terms of intensity of usage of ICT-Mobile Phone functions, facilities, and apps. Meanwhile, their ICT-Mobile Phone engagement seemsto be high in digital maturity for the indispensable characteristics and functions of internet. The findings of this study have implications on ICT system and apps providers on the needs of the users. This is crucial in order to achieve digital maturity which will prepare the grounds for digital inclusion in a digital economy.